Mathematical Communication skills through E-Learning Platforms: Covid19 affect - Sa'ida Tawfiq Marei; Awad Faek Altarawneh (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: This study aimed to investigate the availability of mathematical communication skills through e-learning platforms: the effect of Corona pandemic. Methods: A descriptive approach was used. A questionnaire for mathematical communication skills was constructed, consisting of (37) items. A sample of the students of Hashemite University consisted of (1492) male and female students. Results: The results showed that the availability level of mathematical communication skills through electronic platforms in the educational learning process, in general, is high, and there is a statistically significant difference in All skills of mathematical communication according to the variable of the college, in favor of members of the study sample students from the College of Information Technology when compared to their peers in the College of Educational Sciences. There is a statistically significant difference in skills (speaking, listening) in favor of the study sample students from the College of Engineering when compared to their peers in the College of Educational Sciences. the results showed statistically significant differences between the arithmetic averages of the responses of the study sample students about the effectiveness of electronic platforms in the educational and learning science under the current circumstances (Corona crisis) considering all mathematical communication skills, attributed to the gender variable and for the benefit of males. Conclusions: In light of the study results, it is recommended to work on training students and staff faculties for the optimal use of e-learning platforms, and to develop specialized training programs to design interactive e-learning environments that help activate mathematical communication skills.